Feasibility, Risk Profile and Diagnostic Yield of Stereotactic Biopsy in Children and Young Adults with Brain Lesions - Hamisch, Christina; Blau, Tobias; Klinger, Katharina; Kickingereder, Philipp; Ruess, Daniel; Galldiks, Norbert; Berthold, Frank; Simon, Thorsten; Grau, Stefan; Ruge, Maximilian I. (Klinische Pädiatrie, 2017)
Objective To evaluate the feasibility, safety, and diagnostic yield of stereotactic biopsy (SB) in children and adolescents with cerebral lesions.Methods We performed a systematic review of the literature and a retrospective analysis of all pediatric and adolescent patients who underwent SB for unclear brain lesions at our center. We collected patient and lesion-associated parameters, analysed the rate of procedural complications and diagnostic yield.Results Our institutional series consisted of 285 SBs in 269 children and young adults between 1989 and 2016 (median age, 9 (range 1–18) years). There was no procedure-related mortality. Permanent and transient morbidity was 0.7% and 5.8%, respectively. Lesions were located in brain lobes (26.3%) and in midline structures (73.7%). The diagnostic yield was 97.5% and histology consisted low-grade gliomas (44.2%), high-grade gliomas (15.1%), non-glial tumors (22.8%), and non-neoplastic disease (15.4%). Morbidity was not associated with tumor location, age, histology or intraoperative position of the patient. In order to compare our findings with previous reports, we reviewed 25 studies with 1 109 children and young adults which had underwent SB. The diagnostic yield ranged between 83% and 100%. The reported morbidity and mortality rates range from 0–27% and 0–3.3%, respectively.Conclusions SB in this particular patient population is a safe and a high-yield diagnostic procedure and indicates therefore its importance in the light of personalized medicine with the development of individual molecular treatment strategies.
Keywords: stereotaktische Biopsie; pädiatrische Hirntumoren; Morbidität; diagnostische Ausbeute; Sicherheit